New Student Study Orientation / OSMB Cointainment of Student Independent Character Education: Case Study: Action Social New Student for IT Science for Cointainment Of Indenpendent Character (Open Society Conference, 2023)
Community facts suggest that the process of increasing students' understanding of UT content needs to be improved as it is not well understood. The research gap for this study is the lack of understanding among students about what the UT catalog is, and it is argued that the main reason for many students' errors is incorrect enrollment details, providing new students with academic information regardless of UT. While studying at UT, they pass OSMB Learn about educational services and service management. The purpose of OSMB training for new students is to provide knowledge and understanding of UT, such as online enrollment, how to study at UT, and time management. For new students to learn about UT's academic and administrative services as they begin teaching and learning. This study took a good research methodology and focused on the type of research because this case is very interesting and of public interest, especially central UT. An effective research method is a research process that produces descriptive information in the form of speech or writing with the behavior of the visual. The data collection process for this study was a snowball of students and administrators using an in-depth interview process. To support the conduct of the research, the researchers used Weber's Theory of Social Action research. The novelty of the study is that, according to UT's education policy, OSMB education should improve the outcomes of Open University students.